A new species of the highland frog genus Holoaden (Amphibia, Strabomantidae) from cloud forests of southeastern Brazil - Martins, Itamar A.; Zaher, Hussam (Zootaxa, 2013)
A new species of the genus Holoaden is described from the Atlantic forest of the state of São Paulo, Brazil, being restricted to primary or slightly disturbed high altitude cloud forests along the northeastern portion of the Serra do Mar. The typelocality is determined as Estação Ecológica de Bananal, in the Municipality of Bananal, State of São Paulo, Brazil. The new species is characterized by its moderate body size (female 42.6–44.2 mm SVL; male 37.2–38.5 mm SVL) with long and slender limbs, a head wider than long, a highly glandular dorsum, covered by well developed macroglands that extend to the internasal region, thigh and tibia, and an intense dark brown dorsal coloration and dark grey ventral surface.